Water And Sanitation Impact in the Human Health of Nepal: A Review - Ghimire, Mayanath (GS WOW: Wisdom of Worthy Research Journal, 2025)
This research investigates the influence of water supply and sanitation on human health in Nepal using a systematic evaluation and scientific synthesis of pertinent material. The results show that protecting public health requires good wastewater treatment, efficient pumping systems, safe drinking water, and good water, sanitation, and hygiene (WASH) practices. However, developing countries like Nepal still have problems because they don’t have enough resources or infrastructure. Nepal’s laws and policies encourage the development of WASH. For example, 99.7% of families have toilet facilities, and 95.7% wash their hands with soap after handling trash. Most rural and peri-urban populations get their water via community-managed systems. Even though there has been a lot of development, there are still gaps in services. For example, 7.3% of hospitals and 23% of schools do not have access to water. The country has 17,232 health facilities and 155,650 health workers, including 34,910 doctors, 82,471 nurses, 37,420 auxiliary nurse midwives, and 849 foreign nurses. Income and education are two socioeconomic factors that have a big effect on WASH practices and health outcomes. Environmental stresses, like groundwater depletion in the Terai region and drying of hillregion springs, make water scarcity worse, make systems less reliable, and raise the risk of waterborne diseases like diarrhea. To lower disease rates and improve public health in Nepal, it is important to strengthen WASH infrastructure, raise community knowledge, and carry out targeted interventions in rural areas and schools.